GloPID-R report on Chikungunya, O'nyong-nyong and Mayaro virus, part I: Biological diagnostics - Pezzi, Laura; Reusken, Chantal; Jänisch, Thomas (Antiviral research, 2019)
The GloPID-R (Global Research Collaboration for Infectious Disease Preparedness) Chikungunya (CHIKV), O'nyong-nyong (ONNV) and Mayaro virus (MAYV) Working Group is investigating the natural history, epidemiology and medical management of infection by these viruses, to identify knowledge gaps and to propose recommendations for direct future investigations and rectification measures. Here, we present the first report dedicated to diagnostic aspects of CHIKV, ONNV and MAYV. Regarding diagnosis of the disease at the acute phase, molecular assays previously described for the three viruses require further evaluation, standardized protocols and the availability of international standards representing the genetic diversity of the viruses. Detection of specific IgM would benefit from further investigations to clarify the extent of cross-reactivity among the three viruses, the sensitivity of the assays, and the possible interfering role of cryoglobulinaemia. Implementation of reference panels and external quality assessments for both molecular and serological assays is necessary. Regarding sero-epidemiological studies, there is no reported high-throughput assay that can distinguish among these different viruses in areas of potential co-circulation. New specific tools and/or improved standardized protocols are needed to enable large-scale epidemiological studies of public health relevance to be performed. Considering the high risk of future CHIKV, MAYV and ONNV outbreaks, the Working Group recommends that a major investigation should be initiated to fill the existing diagnostic gaps.
Gesehen am 01.07.2019